2016
DOI: 10.1103/physreve.94.022408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RNA branching on the electrostatic stabilization of viruses

Abstract: Many single-stranded (ss) RNA viruses self assemble from capsid protein subunits and the nucleic acid to form an infectious virion. It is believed that the electrostatic interactions between the negatively charged RNA and the positively charged viral capsid proteins drive the encapsidation, although there is growing evidence that the sequence of the viral RNA also plays a role in packaging. In particular the sequence will determine the possible secondary structures that the ssRNA will take in solution. In this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 50 publications
(118 reference statements)
4
55
0
Order By: Relevance
“…While previous theoretical studies have focused on the scaling behavior of linear and branched flexible polymers [32,34,35,48,[56][57][58], in this paper we study the impact of the stiffness or Kuhn length on the encapsidation of RNA by capsid proteins. In general the duplexed segments of viral RNA contain on average about five to six base-pairs [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While previous theoretical studies have focused on the scaling behavior of linear and branched flexible polymers [32,34,35,48,[56][57][58], in this paper we study the impact of the stiffness or Kuhn length on the encapsidation of RNA by capsid proteins. In general the duplexed segments of viral RNA contain on average about five to six base-pairs [11].…”
Section: Discussionmentioning
confidence: 99%
“…Following these experiments a number of simulation studies, using quenched (fixed) branched polymers as a model for RNA, have shown that the optimal length of encapsidated RNA increases when accounting for its secondary structure [12,33]. Mean-field calculations using annealed (equilibrium) branched polymers as model RNAs have also shown that the length of encapsidated polymer increases as the propensity to form larger numbers of branched points increases [32,34,35]. More importantly, these calculations show that a higher level of branching considerably increases the depth of the freeenergy gain associated with the encapsulation of RNA by a positively charged shell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we have studied the phenomena of overcharging observed in many viruses. Previous mean-field theories as well as the experimental studies of CCMV capsid proteins with short linear polymers have indicated the resulting VLPs are undercharged [24,25,[37][38][39][40]. However, MD simulations revealed overcharging can happen even for linear polymers and the question is why [22].…”
Section: Charge Ratiomentioning
confidence: 99%
“…where ∆ = E 1 − E 0 is the energy gap, and the function R(r, s) is the remainder of the expansion. When s∆ 1, the second term above becomes exponentially negligible, and we may write q(r, s) = e −E0s q 0 ψ 0 (r) (22) and then Eqs. 20, 19 and 7 become respectively equal to…”
Section: Ground State Dominance Approximationmentioning
confidence: 99%